Virtual Education and Teaching Performance in a Peruvian Public University - Reyes Mejía, Mario Gustavo; Lavanda Reyes, Flor Angélica; Ruiz Reyes, Rosa Elvira; Castillo Samanamud, Luis Alberto; Reyes Ruiz, Julia Luzmila (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The San Luis Gonzaga National University, Ica-Peru, due to Covid 19, adapted to virtuality by implementing the Laureasea virtual classroom. This research was carried out during the academic semester 2021-1. Objective: to analyze how virtual education improves teaching performance; 430 teachers from the 24 faculties participated, they answered a virtual survey. Significant result: 80% taught a virtual class for the first time, 60% had access to a virtual classroom, 68% have improved their performance and 75%prefer face-to-face classes. Conclusions: virtual education significantly improves teaching performance and they prefer face-to-face classes.